KARAKTER BANGSA: BUDAYA KOMUNIKASI DALAM KOMUNITAS - Bawa Toron, Vinsensius (STP St. Bonaventura Medan, 2020)
The culture of communication in the family community means that each person will know what love, affection and sacrifice are. Instilled in love and sacrifice appears to be a common interest, similarity, affinity. The family as a small institution and a gift from God, the key to harmony starts from within the family, such as placing trust, setting an example or role model so that children are interested or interested in what they emulate and emulate. Therefore, the key to achieving harmony in the family is to build a culture of continuous communication